2023
DOI: 10.3390/molecules28134925
|View full text |Cite
|
Sign up to set email alerts
|

Widely Targeted Metabolomics Reveals the Effects of Soil on the Metabolites in Dioscorea opposita Thunb.

Abstract: Chinese yam (Dioscorea opposita Thunb. cv. Tiegun), a type of homologous medicinal plant, mainly grows in sandy soil (SCY) and loessial soil (LCY). However, the effects of the soil on the metabolites in SCY and LCY remain unclear. Herein, this study aims to comprehensively elucidate the metabolites in SCY and LCY. A UPLC-MS/MS-based, widely targeted metabolomics approach was adapted to compare the chemical composition of SCY and LCY. A total of 988 metabolites were detected, including 443 primary metabolites, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 45 publications
(55 reference statements)
0
0
0
Order By: Relevance
“…The number of metabolites identified in Oresitrophe rupifraga exceeded those in previous related studies. Studies have been conducted on fruits [ [15] , [16] , [17] ], leaves [ 18 , 19 ], roots [ 20 , 21 ], and bulbs [ 22 ] of plants. In these studies, the number of identified metabolites varied from 403 to 1088.…”
Section: Resultsmentioning
confidence: 99%
“…The number of metabolites identified in Oresitrophe rupifraga exceeded those in previous related studies. Studies have been conducted on fruits [ [15] , [16] , [17] ], leaves [ 18 , 19 ], roots [ 20 , 21 ], and bulbs [ 22 ] of plants. In these studies, the number of identified metabolites varied from 403 to 1088.…”
Section: Resultsmentioning
confidence: 99%